Enhanced covalent interface, crosslinked network and gas barrier property of functionalized graphene oxide/styrene-butadiene rubber composites triggered by thiol-ene click reaction. (15th September 2020) - Zheng, Long; Jerrams, Stephen; Su, Tian; Xu, Zongchao; Zhang, Liqun; Liu, Li; Wen, Shipeng
Abstract: The high gas barrier property of a rubber composite is of great significance for reducing the exhaust gas emissions due to tire rolling resistance and hence the contribution this factor makes to environmental protection. Enhanced covalent interfaces and crosslinked networks are crucial to the gas barrier property of rubber composites. In this research, γ-mercaptopropyltriethoxysilane (MPS) modified GO (MGO)/styrene-butadiene rubber (SBR) composites were prepared by a synergetic strategy of latex compounding method and thiol-ene click reaction. It was found that the mercapto groups in MGO reacted with the vinyl groups in SBR molecules through thiol-ene click reaction during the crosslinking process at 150 °C, thus forming strong chemical interactions at the interface in the form of GO-MPS-rubber and enhanced crosslinked networks. Meanwhile, the strong interface promoted the dispersion of MGO in SBR. The uniform dispersion of MGO, strong interface between MGO and SBR molecules and enhanced crosslinked networks resulted in improved mechanical and gas barrier properties. When filling 5 phr fillers, the tensile strength and gas barrier properties of an MGO/SBR composite improved by 19.0% and 37.5%, respectively, relative to the comparing GO/SBR composite. Graphical abstract: Image 1